Globalization and Cultural Resilience: Transformations and Challenges in India - Tirkey, C. Anupa (Stallion Journal for Multidisciplinary Associated Research Studies, 2022)
Globalization has emerged as a defining phenomenon of the 21st century, influencing economies, societies, and cultures worldwide. India, with its rich cultural heritage and diverse societal fabric, has experienced profound transformations under the influence of globalization. This paper explores the cultural changes and challenges that have emerged in India during this era. It examines how globalization has affected traditional values, societal norms, and cultural practices, and analyzes the resulting tensions between modernity and tradition. The study also discusses how India navigates these challenges, leveraging its cultural resilience and adaptability to foster a hybrid identity in a globalized world.